Efeito de distintas cores de lâmpadas de LED na produção e no comportamento de frangos de corte - Paixão, Sandro José (2014)
The Brazilian production of broilers has reached high levels of production and exportation,gaining leadership on the world exports. This is all due to numerous factors, such as genetic improvement, the ambience, nutrition and other factors related to the welfare and health of the birds. The natural lighting where most birds were raised, both broiler breeders and broilers, has been almost entirely migrated to the artificial form of illumination. Currently there are different sources of roviding artificial lighting, either by the wavelength (color of light), as well as by the lamp itself (fluorescent, incandescent, sodium vapor, LED, etc.). The type of artificial lighting used can increase or reduce energy consumption, but can also affect the behavior and productive performance of the birds. In many cases, the lightning system most often found in aviaries consists of a large number of high-powered lamps, but with a low luminous efficiency. One way to try to minimize this installed load and reduce electricity costs, is using lamps that have a better luminous efficiency, such as fluorescent lamps and LED (Light-Emitting Diode) lamps. In this context, the objective of this study is to address through a literature review, the importance of different colors of LED lighting in zootechnical and behavioral indices of broilers, as well as to address the importance of using new technologies. To this end, it was prepared a chapter of literature review, highlighting he importance of poultry production in the world and justifying the importance of the topic. The second chapter addresses the theme: "Effect of different colors of LED lamps in the production and behavior of broilers and its influence on electricity costs in the activity."